2020
DOI: 10.1136/bmjqs-2019-010206
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of the prevalence and clinical and economic burden of medication error in England

Abstract: ObjectivesTo provide national estimates of the number and clinical and economic burden of medication errors in the National Health Service (NHS) in England.MethodsWe used UK-based prevalence of medication errors (in prescribing, dispensing, administration and monitoring) in primary care, secondary care and care home settings, and associated healthcare resource use, to estimate annual number and burden of errors to the NHS. Burden (healthcare resource use and deaths) was estimated from harm associated with avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
248
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(262 citation statements)
references
References 28 publications
8
248
0
6
Order By: Relevance
“…The epidemiology and aetiology of medication errors are multifactorial and poorly understood, and we believe that this is the first systematic review specific to intravenous medication administration errors in the UK. This review is timely in that it comes after the publication of the Department of Health review of the prevalence of medication errors in the NHS in England 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemiology and aetiology of medication errors are multifactorial and poorly understood, and we believe that this is the first systematic review specific to intravenous medication administration errors in the UK. This review is timely in that it comes after the publication of the Department of Health review of the prevalence of medication errors in the NHS in England 25…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of this focused review broadly align with the findings of other work. Elliott et al 25 identified that medication administration errors account for 54% of medication errors overall in England. Furthermore, Elliott’s review identified the elderly and children and young people as at-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO estimates that half of all drugs are incorrectly prescribed, stored, administered or used [6]. Studies have shown that up to 30% of patients are exposed to a potential medication error, and that half of these errors occur during administration of the drug [2,7,8]. In outpatient care, speci c medication errors include taking the wrong dose or quantity of a particular drug as well as omission of a drug or taking unlicensed drugs [9].…”
Section: Introductionmentioning
confidence: 99%
“…In England it is estimated that over 237 million medication errors occur every year. This incurs extra costs of approximately 108 million euros for the NHS, as longer hospital stays or admissions are necessary [8,14]. In Germany, the annual costs incurred by medication errors are estimated to be over one billion euros [15].…”
Section: Introductionmentioning
confidence: 99%
“…Medicines are integral to the prevention, treatment and management of health, but there is growing evidence of a need to improve medication safety . Regarding hospitalised patients in England, it has been estimated that the prescribing error rate is almost 9%, and that 1 in 7 patients experience harm from their medicines …”
Section: Introductionmentioning
confidence: 99%